Reference services - Sharma, S. K. (Shree, 2005)
Contents of material: 1/ Introduction. 2/ Library services provision. 3/ Reference resousces. 4/ Reference classification. 5/ Librarianship in reference services. 6/ Trends in reference services. 7/ Digital reference services. 8/ Online reference service. 9/ Competencies of librarianship. 10/ Future of reference services.